Utilization of Electronic Learning Facilities (Studies in the Department of Office Governance Automation at SMKN 1 Wajo) - Saleh, Sirajuddin; Darwis, Muh.; Ar, Nur Annisa (Universitas Negeri Makassar, 2022)
To complement existing facilities, Teaching and Learning Activities (KBM) can be said to run well if the availability of learning facilities is adequate and appropriate to use because basically, the success of learning in schools is supported by the effective utilization or utilization of existing learning facilities in the school itself. efficient. This study aims to determine the use of learning facilities in the Office Administration Automation Department at UPT SMKN 1 Wajo. This study uses a quantitative method with a descriptive approach. Data collection techniques were carried out in the form of observation, questionnaires, and documentation techniques. With a population of 177 people and a sample of 53 people who are students of the OTKP Department at UPT SMKN 1 Wajo. The data analysis in this study uses the percentage formula so that the data obtained from the research results are processed by the percentage of each question choice in the questionnaire. In the implementation of this research, there are 3 indicators of the use of learning facilities, namely: learning tools, teaching aids, and learning media. The results showed that the use of learning facilities based on indicators of learning tools got a percentage of 73.87% which was included in the effective category, and teaching aids indicators of 63.96% or included in the effective category and indicators of learning media reached a percentage level of 64.90%. which is included in the effective category.